2008
DOI: 10.1016/j.ntt.2007.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal methamphetamine use and neonatal neurobehavioral outcome

Abstract: Background-Methamphetamine (MA) use among pregnant women is an increasing problem in the United States. How prenatal MA exposure affects neonatal neurobehavior is unknown.Objective-To examine the neurobehavioral effects of prenatal MA exposure.Design-The Infant Development, Environment and Lifestyle (IDEAL) study screened 13,808 subjects and 1632 were eligible and consented. 166 (n=74 exposed) were enrolled in a longitudinal follow up. Exposure was determined by meconium assay and self-report with alcohol, mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
127
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(132 citation statements)
references
References 38 publications
4
127
0
1
Order By: Relevance
“…4 More recently, the NNNS has been used to describe neurobehavior among infants with other prenatal exposures or risk factors. 2,[5][6][7][8][9][10][11][12][13] The time of newborn examination reported in published studies ranges widely from several hours to several weeks, and no recommendation has been made as to the earliest age of reliable assessment. An early examination seems desirable because it may provide more valuable information on the immediate effects of prenatal exposures or other risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 More recently, the NNNS has been used to describe neurobehavior among infants with other prenatal exposures or risk factors. 2,[5][6][7][8][9][10][11][12][13] The time of newborn examination reported in published studies ranges widely from several hours to several weeks, and no recommendation has been made as to the earliest age of reliable assessment. An early examination seems desirable because it may provide more valuable information on the immediate effects of prenatal exposures or other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The primary purpose of the Maternal Lifestyles Study, 3 for which the NNNS was developed, was to examine the impact of prenatal exposure to cocaine and/or opiates on health and neurobehavioral outcomes from infancy through adolescence. 4 Subsequently, the NNNS has been used in studies of prenatal exposure to other substances such as methadone, 5 methamphetamine, 6 marijuana, 7 and tobacco. [8][9][10] It also has been used to identify the impact of being small for gestational age, 11 adolescent parenting, 12 and maternal depression 13 on infant neurobehavior.…”
mentioning
confidence: 99%
“…Such abnormal brain development may account for the slower maturation of behavioral measures observed in neonates with prenatal methamphetamine exposure. 16,17 While the exact mechanism of how prenatal methamphetamine exposure may lead to lower brain diffusivity is unknown, lower WM diffusivity typically reflects more compact axonal fibers. Consistent with this interpretation, children with prenatal methamphetamine exposure showed smaller subcortical structures.…”
Section: Thalamus (E) Globus Pallidus (F) Putamen (G) Caudate (H)mentioning
confidence: 99%
“…3 Research on the impact of prenatal MA exposure on child development is emerging from the only large, prospective longitudinal study of prenatal MA use, the Infant Development, Environment, and Lifestyle (IDEAL) study. 4 Previous MA findings from IDEAL include increased small for gestational size at birth 5 and decreased length through 3 years, 6 poor quality of movement, low arousal, and increased stress signs in the newborn period 7 and poor grasping ability at 1 and 3 years of age. 8 The only comparable study conducted in Sweden showed increased drowsiness during the newborn period 9 and increased behavior problems in amphetamineexposed children.…”
mentioning
confidence: 99%